Graphical interface for mobile robot navigation using distance transform - Li, Yinghua. (2008)
This thesis presents three programs for simulating path planning using Distance Transform method for mobile robot navigation. The three programs address the problem of finding optimal paths through known stationary environment and initially unknown stationary environment, respectively.